2001
DOI: 10.1093/chromsci/39.9.370
|View full text |Cite
|
Sign up to set email alerts
|

Separation and Determination of Ephedrine Alkaloids and Tetramethylpyrazine in Ephedra sinica Stapf by Gas Chromatography-Mass Spectrometry

Abstract: A simple, sensitive, and reliable method using gas chromatography (GC)-mass spectrometry (MS) is developed for the simultaneous determination of ephedrine alkaloids and 2,3,5,6-tetramethylpyrazine (TMP) in Ephedra sinica Stapf. The sample is extracted with ethyl ether and submitted to GC-MS for identification and quantitation without derivatization. The column used for GC is an HP-5 (30.0 m x 250 microm x 0.25 microm, 5% phenyl methyl siloxane), and the carrier gas is helium. The detection limits for ephedrine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…In recent years, they have become increasingly popular among drug abusers owing to well‐organized publicity on the Internet. The main pharmacologically active ingredients of the Ephedra species are the alkaloids ephedrine (EP) and pseudoephedrine (PEP) as well as norephedrine (NE), norpseudoephedrine (NPE, cathine), methylephedrine (ME), and methylpseudoephedrine (MPE) 5–8. These compounds are potent CNS stimulants and also have a sympathomimetic effect on the peripheral nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, they have become increasingly popular among drug abusers owing to well‐organized publicity on the Internet. The main pharmacologically active ingredients of the Ephedra species are the alkaloids ephedrine (EP) and pseudoephedrine (PEP) as well as norephedrine (NE), norpseudoephedrine (NPE, cathine), methylephedrine (ME), and methylpseudoephedrine (MPE) 5–8. These compounds are potent CNS stimulants and also have a sympathomimetic effect on the peripheral nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…A recent survey revealed that few methods were available for the determination of TMP in pharmaceutical preparations, botanical or biological samples, which involved liquid chromatography with ultraviolet detection [4][5][6][7][8] and gas chromatography-mass spectrometry [9][10][11]. No analytical methods were available for the simultaneous determination of TMP and HTMP or individual determination of HTMP in biological samples.…”
Section: Introductionmentioning
confidence: 99%
“…The chromatography conditions 17 and retention time of ephedrine and its degradation products are listed in Table 1. Mass determination of the degradation products in the samples were analyzed by HPLC (Waters Alliance 2795, Milford, Massachusetts) with diode array detection (Waters 996 PDA) and single quadrupole mass spectrometry (Waters ZQ), using electrospray in both positive and negative ionization modes, and 90-400 amu ion scanning.…”
Section: Hplc and Liquid Chromatography-mass Spectrometry Methodsmentioning
confidence: 99%